Mechanical behaviours of bedded sandstone under hydromechanical coupling - Junwen Zhang; Zhixiang Song; Lichao Zhang; Shaokang Wu; Shanyong Wang; Yang Zhang; Xukai Dong; Jinxin Wang; Yanbo Han; Baohua Kan (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
The combination of the dipping effect and hydromechanical (H-M) coupling effect can easily lead to water inrush disasters in water-rich roadways with different dip angles in coal mines. Therefore, H-M coupling tests of bedded sandstones under identical osmotic pressure and various confining pressures were conducted. Then, the evolution curves of stress-strain, permeability and damage, macro- and mesoscopic failure characteristics were obtained. Subsequently, the mechanical behaviour was characterized, and finally the failure mechanism was revealed. The results showed that: (1) The failure of the sandstone with the bedding angle of 45° or 60° was the structure-dominant type, while that with the bedding angle of 0°, 30° or 90° was the force-dominant type. (2) When the bedding angle was in the range of (0°, 30°) or (45°, 90°), the confining pressure played a dominant role in influencing the peak strength. However, within β∈(30°, 45°), the bedding effect played a dominant role in the peak strength. (3) With the increase in bedding angle, the cohesion increased first, then decreased and finally increased, while the internal friction angle was the opposite. (4) When the bedding angle was 0° or 30°, the “water wedging” effect and the “bedding buckling” effect would lead to the forking or converging shear failure. When the bedding angle was 45° or 60°, the sliding friction effect would lead to the shear slipping failure. When the bedding angle was 90°, the combination of the “bedding buckling” effect and shear effect would lead to the mixed tension-shear failure. The above conclusions obtained are helpful for the prevention of water inrush disasters in water-rich roadways with different dips in coal mines.